Vietnam - Clark, Sarah, ....-; Zglinicki, Maciej, ....- (Zeewolde : Cambium, 2016)
This Insight Guide is a lavishly illustrated inspirational travel guide to Vietnam and a beautiful souvenir of your trip. Perfect for travellers looking for a deeper dive into the destination's history and culture, it's ideal to inspire and help you plan your travels. With its great selection of places to see and colourful magazine-style layout, this Vietnam guidebook is just the tool you need to accompany you before or during your trip. Whether it's deciding when to go, choosing what to see or creating a travel plan to cover key places like Ho Chi Minh City and Hanoi, it will answer all the questions you might have along the way. It will also help guide you when you'll be exploring Hoi An or discovering Phu Quoc on the ground.